2006
DOI: 10.1007/s10902-005-2748-7
|View full text |Cite
|
Sign up to set email alerts
|

Hope I Die before I Get Old: Mispredicting Happiness Across the Adult Lifespan

Abstract: aging, well-being, affective forecasting,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 25 publications
1
41
1
6
Order By: Relevance
“…Both of these factors potentially limit the generalizability of our results, although we do not have a specific reason to think that the associations observed would be different in a more representative sample. (Note: In a separate study using the same internet methods, and similar response rates, sample, etc, we found age-related trends in happiness that mirror those found in more representative samples (Lacey, Smith, & Ubel, 2006). )…”
Section: Discussionsupporting
confidence: 70%
“…Both of these factors potentially limit the generalizability of our results, although we do not have a specific reason to think that the associations observed would be different in a more representative sample. (Note: In a separate study using the same internet methods, and similar response rates, sample, etc, we found age-related trends in happiness that mirror those found in more representative samples (Lacey, Smith, & Ubel, 2006). )…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, our previous research using this panel has shown that Internet survey responses closely match those of representative samples. [24] Second, our scenario was entirely hypothetical, and the reactions of actual mothers-to-be may differ. We do not claim that our estimates of perceived risk and intentions to pursue amniocentesis correspond to those of patient populations.…”
Section: Commentmentioning
confidence: 99%
“…Cuando las investigaciones incluyen también la exploración de aspectos positivos nos encontramos con hallazgos inesperados para un paradigma deficitario, que muestran de manera reiterada que en la vejez también hay ganancias. Entre ellas, las que se han centrado en el estudio de variables como la felicidad (Lacey, 2006;Wood, Kisley & Burrows, 2007), el bienestar (Arias & Soliverez, 2009;Mroczek & Kolarz, 1998;Okun & Stock, 1987), la sabiduría (Baltes & Freund, 2007) y las fortalezas en la vejez (Arias, Castañeiras & Posada, 2009) han aportado evidencia al respecto.…”
Section: Conclusionesunclassified